Determinants of Patient Safety Culture: The Role of Safety Leadership Interactions - Setiawan, Eka; Kusumapradja, Rokiah (Jurnal Manajemen dan Organisasi, 2024)
This research was motivated by several problems related to patient safety in central surgical installations. The aim of this research is to empirically reveal the influence of interprofessional collaboration and implementation of the surgical safety checklist on patient safety culture with safety leadership as a moderating variable. This research is included in quantitative research with a cross sectional study design, the population is health workers in central surgical installations, the sampling technique uses saturated samples so that the sample size is 77 respondents using a purposive sampling method. The analytical method used is three box method analysis and PLS-SEM. The results of the analysis concluded that interprofessional collaboration, the application of the Surgical Safety Checklist and Safety Leadership had a positive and significant effect on patient safety culture. Safety Leadership was not able to moderate interprofessional collaboration but positively moderated the application of the Surgical Safety Checklist to patients. patient safety culture.